Analisis Kewirausahaan Usaha Makeup Dan Skincare Di Kota Palu - Hattab, Syahruddin; Zaenong, Nur fadhilah Dwi Putri; Ananda, Syafikah Davina; Petonengan, Devi; Fina (JPS: Journal of Publicness Studies, 2026)
The skincare industry has experienced rapid growth along with increasing public awareness of skin care and the self-care lifestyle. This condition creates both opportunities and challenges for business actors, particularly micro, small, and medium enterprises (MSMEs). This study aims to analyze business planning, product and service innovation, marketing strategies, and challenges faced by makeup and skincare businesses through the Entrepreneurship Field Experience Program (PPL). The research method used is a qualitative descriptive approach, with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that skincare businesses are able to survive and grow through personalized services, product adjustments based on market trends, and the utilization of social media as a marketing tool. The main challenges include price competition with online stores and limited stock availability from distributors. This study concludes that service innovation, understanding consumer needs, and adaptability to trends are key factors for the success of MSME-scale skincare businesses.